ANALISIS PENGENDALIAN ARUS DAN KARAKTERISTIK DARI REFLOW SOLDERING - Dian Anjarwati; Insani Abdi Bangsa (Universitas Islam Lamongan, 2023)
Solder is a tool that serves to solder electronic components. Each electronic component has its own resistance, one of which is resistance to high temperatures. Of the types of electronic components that tend to have the lowest resistance to high temperature, SMD components are needed so that soldering tool is needed that is able to control the temperature according to the characteristics of the electronic components. In its design,this tools uses an Arduino Uno ATMega328 microcontroller as a system controller as well as several other supporting components such as aK-Type Thermocouple sensor and a relay as a temperature controller that is generated for soldering. The working system of this tool can be adjusted through the set point as the input given to the tool. The input is the carried out by the microcontroller and he instructs the sensor to start flowing heat according to the input value given. In this study, the maximum temperature reached to start heating is 11.5 C and the lowest temperature is 32.5 C, the difference between to the temperatures is 79 C and the resolution in the calculating of the measurement is 100 ms. In the results of temperature control, the smaller the delay value given, the greater the risetime value.